Mathematics teacher education in Zimbabwe - Mtetwa, David; Nyikahadzoyi, Maron; Nyaumwe, Lovemore J.; Chauraya, Million; Kwari, Rudo; Mukono, Shadreck (Marang Centre for Mathematics and Science Education, 2020)
When Zimbabwe gained her independence in 1980 the new government took aggressive and positive steps to redress historical imbalances. The education sector was democratised . Access and provision of education became available to the majority of school going age children in the country . All teacher education institutions became associate colleges of the University of Zimbabwe.....................................